A SURVEY OF DEPRESSION AMONG IRANIAN MEDICAL STUDENTS AND ITS CORRELATION WITH SOCIAL SUPPORT AND SATISFACTION - Talaei, Ali; Ardani, Amir Rezaei; Saghebi, Ali (Journal of Pakistan Psychiatric Society, 2008)
Objective: To investigate the correlation between depression and level of social support and satisfaction in Iranian medical students.Design: Descriptive-analytic and cross-sectional studyPlace and duration of study: The study was carried out on the students of Mashhad University of Medical Sciences in 2004 and 2005.Subjects and Method: Self administered questionnaires about socio-demographic information (age, gender, marital status, educational level) and satisfaction (satisfaction with the educational staff, university employees and environmental facilities), Beck Depression Inventory (BDI) and Cassidy social support scale were given to students who were selected by multi stage randomized sampling. The data were analyzed by SPSS version 14 using especially the x2-test.Results: 796 students answered the questionnaires anonymously (88.84% response rate). A total of 53% of participants had depression (38.3% mild, 10.2% moderate and 4.5% severe type). No associations were found between depression and gender and marital status. Results showed that 8.4%, 32% and 59.6% of participants reported low, moderate and high levels of social support respectively. 46.50% and 47.92% of the students were somewhat satisfied with the educational staff and university employees respectively but 42.05% were strongly dissatisfied with environmental facilities.Conclusions: Depression is more frequent in Iranian medical students than general population. A negative correlation was seen between depression and the level of social support in students and the prevalence of depression had a significant relation with their satisfaction with the educational staff, university employees and their attitude and environmental facilities.